Method for producing heat shrinkable film
By using powders and re-granulates obtained from printed heat shrink films, a new heat shrink film is prepared, which solves the problem that it is difficult to effectively utilize the printed superheated shrink film in the prior art, and realizes the recycling of resources and the maintenance of the performance of the heat shrink film.
Patent Information
- Application Number
- JP2021102184
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-27
- Filing Date
- 2021-06-21
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2040-09-30
AI Technical Summary
The prior art is difficult to effectively utilize printed heat shrink films as a new resource, especially to remove the problem of printing ink and coating while maintaining the functions and properties of the heat shrink films.
A new heat shrink film is prepared by using powders and repellets obtained from the printed heat shrink films, and the printing ink and coatings in these materials are removed or separated to form a heat shrink film with excellent properties.
The efficient use of printed heat shrink films is achieved without affecting the function and properties of the heat shrink film, which promotes the recycling of resources and reduces the generation of waste.
Smart Images

Figure 0007659362000001 
Figure 0007659362000002 
Figure 0007659362000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat-shrinkable film that can be suitably used as a packaging material for food, beverages, medicines and medical products, chemical products, cosmetics, toiletries, industrial products, agricultural materials, etc. Manufacturing method Regarding. [Background technology]
[0002] Plastic films are used for a variety of purposes, from food, beverages, pharmaceuticals, chemicals, cosmetics, toiletries, and industrial products. However, in recent years, plastic waste and marine pollution have become global social issues. For this reason, there has been interest in the circular economy, which regards plastic products and packaging materials that were previously discarded as new resources and circulates resources without producing waste.
[0003] On the other hand, packaging materials such as food packaging materials and beverage packaging materials are often printed with information such as the ingredient labeling of the contents, the date of manufacture, bar codes, and even the design of the product and the desire to purchase. For example, containers such as PET bottles filled with beverages such as tea and juice are often fitted with heat-shrinkable films printed with printing ink, and the printing is often done on the back side of the film (the surface that contacts the container). Therefore, the heat-shrinkable film is required to be transparent in order to make the contents visible and the letters and patterns printed on the back side visible. In addition, the surface of the heat-shrinkable film (the surface that does not contact the container) is often overcoated to improve the design such as gloss and to prevent scratches.
[0004] Therefore, from the perspective of circular economy, this printed heat-shrinkable film should be viewed as a new resource, and in order to manufacture new heat-shrinkable films, it is important that the functions and properties required of the heat-shrinkable film are not hindered, even if it contains printing inks or overcoats.
[0005] As methods for producing a new heat-shrinkable film using heat-shrinkable film as a raw material, Patent Document 1 discloses a method for producing a film that includes heating scraps of heat-shrinkable film to a temperature equal to or higher than the heat-shrinkage initiation temperature and equal to or lower than the flow initiation temperature to cause the film to shrink and then crushing the scraps, and a method for producing a film that includes crushing scraps of heat-shrinkable film and then heating them to a temperature equal to or higher than the heat-shrinkage initiation temperature and equal to or lower than the flow initiation temperature to cause the film to shrink. Furthermore, Patent Document 2 discloses a heat-shrinkable label printed with an alkali-soluble ink and a method for removing the printed ink from the heat-shrinkable label. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 6-47810 [Patent Document 2] JP 2002-60518 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the method disclosed in Patent Document 1 is a method of recovering edge scraps generated in the trimming process and slitter process after stretching during the manufacturing process of heat shrinkable film and reusing them as raw materials within the manufacturing process, which differs from the perspective of circular economy in which films introduced to the market are recovered as resources.In addition, Patent Document 1 states that the scraps used may be recovered used films, but does not anticipate technical issues that may arise from using printed films, and does not mention any technical ideas for solving the issues.
[0008] Furthermore, the heat-shrinkable label disclosed in Patent Document 2 discloses treatment of the heat-shrinkable label by corona treatment or the like to make the printing ink easier to peel off, and a method for peeling off the printing ink, but does not mention how to solve problems that arise when newly producing a heat-shrinkable film using the heat-shrinkable label as a raw material, or the properties required of a heat-shrinkable film.
[0009] This invention regards printed heat-shrinkable film as a new resource from the perspective of circular economy, and even if it contains printing inks and overcoats, Has excellent appearance The present invention provides a method for producing a heat-shrinkable film. [Means for solving the problem]
[0010] As a result of extensive investigation, the present inventors have found that A specific process was performed Packaging materials A specific amount of at least one of fluff and pellets obtained from This makes it possible to produce a heat-shrinkable film that can solve the problems of the conventional technology. Manufacturing method Thus, the present invention has been completed.
[0011] That is, the present invention provides With printed layer A heat-shrinkable film having at least one layer (I) made of a resin composition (Z1) containing at least one of fluff (Pf) obtained from a packaging material (P) as a starting material and repellets (Pr). Manufacturing method The packaging material (P) and a step of producing a heat-shrinkable film using a resin composition (Z1) containing at least one of the obtained fluff (Pf) and repellet (Pr), wherein the content of at least one of the fluff (Pf) and repellet (Pr) in the resin composition (Z1) is 10% by mass or more and 90% by mass or less. A heat shrinkable film Manufacturing method The first gist is as follows. Effect of the Invention
[0014] The present invention Manufacturing method According to A heat-shrinkable film that does not impair the functions and properties required of a heat-shrinkable film can be obtained. At the same time, products and packaging materials that were previously discarded can be viewed as new resources and can be used effectively to help realize a circular economy society that circulates resources without producing waste. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, the heat shrinkable film, packaging material, molded article, and container of the present invention will be described as an example of an embodiment of the present invention. However, the scope of the present invention is not limited to the embodiment described below.
[0016] In this specification, the term "main component" refers to a component that occupies the largest percentage by mass when the total of the constituent components is 100% by mass, and is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more.
[0017] Furthermore, when it is written "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" and "preferably smaller than Y".
[0018] In this specification, the term "film" is intended to encompass a wide range of materials from thick sheets to thin films.
[0019] In this specification, "at least one direction" means either the longitudinal direction or the transverse direction, or both directions, when the flow direction from the extruder in the production process of the heat shrinkable film is defined as the longitudinal direction (MD) and the perpendicular direction is defined as the transverse direction (TD), and the "main shrinkage direction" means the direction of the longitudinal direction or the transverse direction which has the larger heat shrinkage rate.
[0020] Furthermore, even if the upper and lower limits of the numerical ranges in this specification are slightly outside the numerical ranges specified by the present invention, they are included in the equivalent range of the present invention as long as they have the same action and effect as those within the numerical range.
[0021] [Packaging materials (P)] The heat-shrinkable film according to the first aspect of the present invention has a layer (I) made of a resin composition (Z1) containing at least one of fluff (Pf) and repellets (Pr) obtained using a packaging material (P) as a starting material, and the packaging material (P) has a printed layer. In addition, the heat-shrinkable films according to the second and third aspects of the present invention have a layer (I) made of a resin composition (Z1) containing at least one of fluff (Pf) and repellets (Pr) obtained using a packaging material (P) as a starting material. The packaging material (P) used in the second and third embodiments may or may not have a printed layer, that is, the packaging material (P) may or may not have a printed layer.
[0022] The form and shape of the packaging material (P) is not particularly limited, and examples thereof include a film-like material, a tubular material in which the ends of a film-like material are bonded by a solvent or heat sealing, a tubular material after shrinkage that is attached to a molded product or container by heat shrinkage, a film-like material that is attached to a molded product or container and then opened along a perforation, or crushed or cut products thereof. Among these, it is preferable to use one that is attached to a molded product or container from the viewpoint of circular economy.
[0023] The history of the packaging material (P) is not particularly limited, and may be any history, such as a product distributed in the market, unused product, intermediate processing product, leftover product, defective product, prototype, discarded product, etc. The packaging material (P) may be a mixture of packaging materials (P) having different printing inks, colors, designs, or resin compositions, or may be packaging materials (P) of the same type.
[0024] Here, from the viewpoint of circular economy, it is preferable that the starting packaging material (P) is a heat-shrinkable film.
[0025] The resin composition constituting the packaging material (P) is not particularly limited. Examples of the resin constituting the packaging material (P) include polystyrene-based resins, polyester-based resins, polyvinyl chloride-based resins, polyolefin-based resins, etc. Among them, the polyester-based resin (A) described below is preferred, and it is more preferred that the packaging material (P) is composed of a resin composition mainly composed of the polyester-based resin (A).
[0026] In the first to third aspects of the present invention, at least one of fluff (Pf) and repellet (Pr) obtained from the packaging material (P) is used. When obtaining the fluff (Pf) and repellet (Pr) from the packaging material (P), it is preferable to carry out at least one of the following processes: printing ink peeling process (a), cutting process (b), crushing process (c), and drying process (d).
[0027] [Printing ink removal treatment (a)] When the packaging material (P) has a printed layer, it is preferable to carry out a printing ink peeling treatment (a). A known method can be used as the printing ink peeling treatment (a). For example, the method disclosed in JP-A-2002-60518, in which the material is immersed in an alkaline aqueous solution and then the printing ink is peeled off, can be suitably used.
[0028] In addition, in this printing ink peeling treatment (a), the packaging material (P) may be treated in a state where it is not attached to a container or the like, or may be treated while the packaging material (P) is attached to a container. Also, the printing ink peeling treatment (a) may be performed after the packaging material (P) is made smaller by cutting treatment (b) or crushing treatment (c) described below in advance, or the cutting treatment (b) or crushing treatment (c) may be performed after the printing ink peeling treatment (a). In addition, in the printing ink peeling treatment (a), it is preferable that the printing ink is completely removed, but it is acceptable for the printing ink to remain.
[0029] [Cutting process (b), crushing process (c)] The methods of the cutting process (b) and the pulverization process (c) are not particularly limited. Examples of the cutting process (b) include a method of cutting with a cutting machine such as a slitter or a shredder. Examples of the pulverization process (c) include a method of pulverization with a pulverizer, a method of pulverization in stages with multiple pulverizers, such as coarse pulverization with a primary pulverizer and then further fine pulverization with a secondary pulverizer, and the like. These cutting processes (b) and pulverization processes (c) may be used alone or in combination of two or more.
[0030] In particular, when fluff (Pf) is obtained from the packaging material (P), it is preferable to subject the packaging material (P) to a crushing process (c) using a crusher. The crusher is preferably a mechanical shearing type. Furthermore, in order to make the packaging material (P) into a size that can be fed to the crusher, it is possible to subject the packaging material (P) to a cutting process (b) and then a crushing process (c).
[0031] The atmospheric temperature in the pulverizer is not particularly limited, and may be room temperature (23°C) or may be heated. When heating in the pulverizer, it is preferable that the temperature is lower than the temperature at which the packaging material (P) melts, specifically, it is preferably 30°C or higher and 150°C or lower, more preferably 40°C or higher and 140°C or lower, and even more preferably 50°C or higher and 130°C or lower. By setting the atmospheric temperature in the pulverizer to the above temperature or higher, it is easy to remove moisture and printing solvent remaining in the packaging material (P), and it is also preferable that it can serve as the drying process (d) described later. In addition, by setting the temperature lower than the above temperature, it is preferable that the fluff (Pf) can be prevented from fusing.
[0032] [Drying process (d)] Since moisture and printing solvent often remain in the packaging material (P), it is preferable to carry out a drying process (d). By carrying out the drying process (d), it is possible to suppress thermal decomposition and thermal deterioration of the packaging material (P), particularly in the melt kneading process in an extruder used to obtain repellets (Pr) or new heat-shrinkable films from the packaging material (P). Furthermore, if a large amount of printing solvent contained in the printed layer remains in the packaging material (P), the printing solvent may volatilize immediately after being fed to the extruder, causing smoke, fire, or explosion, so it is preferable to carry out the drying process (d).
[0033] The drying method of the drying treatment (d) is not particularly limited, but it is preferable to use a hot air dryer or a vacuum dryer.
[0034] The drying temperature and drying time in the drying step (d) are preferably adjusted appropriately depending on the type (boiling point) and amount of the remaining printing solvent. The drying temperature is preferably equal to or lower than the temperature at which the packaging material (P) melts, and more preferably, equal to or higher than 30°C and equal to or lower than 150°C, more preferably equal to or higher than 40°C and equal to or lower than 140°C, and even more preferably equal to or higher than 50°C and equal to or lower than 130°C. By setting the drying temperature at or above the above temperatures, it tends to be easier to remove moisture and printing solvent remaining in the packaging material (P). In addition, by setting the temperature at or below the above temperatures, it tends to be possible to suppress the packaging materials (P) from fusing together in the drying process (d).
[0035] After the drying process (d), the amount of various printing solvents remaining in the packaging material (P) is preferably 60 ppm or less, and the amount of remaining moisture is preferably 400 ppm or less.
[0036] In the present invention, when obtaining at least one of the fluff (Pf) and the repellet (Pr) from the packaging material (P) as a starting material, it is preferable to carry out at least one of the printing ink peeling treatment (a), the cutting treatment (b), the crushing treatment (c), and the drying treatment (d), but the number of times and the order of these treatments are not limited. For example, it is acceptable to carry out the crushing treatment (c) several times in succession and then carry out the drying treatment (d), or to carry out the crushing treatment (c), the drying treatment (d), and then carry out the crushing treatment (c) again.
[0037] Methods that are suitably used for obtaining the fluff (Pf) vary depending on the form, shape, history, and presence or absence of a printed layer of the packaging material (P), but examples include a method of subjecting the packaging material (P) to a crushing process (c) to obtain fluff (Pf), a method of subjecting the packaging material (P) to a crushing process (c) and then a drying process (d) to obtain fluff (Pf), a method of subjecting the packaging material (P) to a printing ink peeling process (a) and then a cutting process (b) or a crushing process (c) and then a drying process (d) to obtain fluff (Pf), a method of subjecting the packaging material (P) to a cutting process (b) or a crushing process (c) and then a printing ink peeling process (a) and then a drying process (d) to obtain fluff (Pf), and a method of subjecting the packaging material (P) to a cutting process (b) or a crushing process (c) and then a printing ink peeling process (a) and then a drying process (d) to obtain fluff (Pf).
[0038] The average particle size of the fluff (Pf) thus obtained is preferably 0.1 mm or more and 25 mm or less, more preferably 0.5 mm or more and 20 mm or less, and even more preferably 1 mm or more and 15 mm or less. If the average particle size of the fluff (Pf) exceeds the above values, the bulk density tends to decrease and the quantitative supply to the extruder tends to decrease. In addition, a large volumetric space is required for storage and transportation, which tends to be undesirable in terms of cost. On the other hand, if the average particle size is less than the above values, supply problems such as blitting tend to occur easily in the supply path to the extruder. In addition, the number of times and time required for crushing tend to be required, which tends to be undesirable in terms of cost.
[0039] In addition, the method suitably used for obtaining the re-pellets (Pr) varies depending on the form, shape, history, presence or absence of a printed layer, etc. of the packaging material (P), but examples thereof include a method of drying the packaging material (P) (d) and then supplying it to an extruder to obtain re-pellets (Pr), a method of cutting the packaging material (P) (b) or crushing it (c) and then supplying it to an extruder to obtain re-pellets (Pr), a method of cutting the packaging material (P) (b) or crushing it (c) and then drying it (d) and then supplying it to an extruder to obtain re-pellets (Pr), and a method of performing a printing ink peeling process (a) on the packaging material (P), then cutting it (b) or crushing it (c), then drying it (d) and then supplying it to an extruder to obtain re-pellets (Pr).
[0040] As a method for obtaining repellets (Pr) by supplying the packaging material (P) to an extruder, a method in which the packaging material (P) is melt-kneaded and the extruded molten resin is cut into pellets is preferable.
[0041] The type of the extruder is not particularly limited, but it is preferably a twin-screw extruder. The extruder is preferably equipped with a vent (degassing) mechanism. Furthermore, when obtaining repellets (Pr), virgin resin raw material may be mixed with the packaging material (P) and fed to the extruder.
[0042] In obtaining the repellets (Pr), the set temperature of the extruder is preferably 150°C or more and 300°C or less, more preferably 170°C or more and 280°C or less, and even more preferably 190°C or more and 260°C or less. If the set temperature of the extruder is less than the above temperature, the starting material made from the packaging material (P) is not preferred because it is difficult to melt and flow. Also, if the set temperature of the extruder exceeds the above temperature, the starting material made from the packaging material (P) may be thermally decomposed, which is also not preferred. In particular, when the packaging material (P) is composed of a resin composition mainly composed of a polyester resin (A) described later, if the set temperature of the extruder exceeds the above temperature, the reduced viscosity and weight average molecular weight of the obtained repellets (Pr) are significantly reduced, which is also not preferred.
[0043] In addition, the method for cutting into pellets is not particularly limited, but for example, a method in which the discharged molten resin is cut into pellets at the discharge port and then cooled to obtain re-pellets (Pr), or a method in which the discharged resin is made into a strand shape and transported while being cooled in a water tank or the like, and the cooled strand is cut into pellets to obtain re-pellets (Pr), etc. are preferably used.
[0044] In this manner, fluff (Pf) and repellets (Pr) are obtained using the packaging material (P) as a starting material.
[0045] When the packaging material (P) is composed of a resin composition mainly composed of a polyester resin (A) described later, the reduced viscosity of at least one of the fluff (Pf) and the repellet (Pr) is preferably 0.4 dL / g or more and 1.5 dL / g or less, more preferably 0.5 dL / g or more and 1.2 dL / g or less, and even more preferably 0.6 dL / g or more and 1.0 dL / g or less. If the reduced viscosity is above the above numerical value, there is a tendency to suppress the deterioration of film strength characteristics and heat resistance. On the other hand, if the reduced viscosity is below the above numerical value, there is a tendency to ensure the fluidity of the molten resin during extrusion. The reduced viscosity can be measured by an automatic viscosity measuring device.
[0046] In addition, when the packaging material (P) is composed of a resin composition mainly composed of a polyester resin (A) described later, the weight average molecular weight of at least one of the fluff (Pf) and the repellet (Pr) is preferably 40,000 to 100,000, more preferably 50,000 to 90,000, and even more preferably 60,000 to 80,000. If the weight average molecular weight is above the above value, the film strength characteristics and heat resistance tend to be suppressed from decreasing. On the other hand, if the weight average molecular weight is below the above value, the fluidity of the molten resin during extrusion tends to be ensured. The weight average molecular weight can be measured using gel permeation chromatography (GPC).
[0047] The heat-shrinkable films according to the first to third aspects of the present invention are heat-shrinkable films having at least one layer (I) made of a resin composition (Z1) containing at least one of the thus obtained fluff (Pf) and repellets (Pr).
[0048] On the other hand, when using fluff (Pf) or repellet (Pr) obtained from the packaging material (P) as a starting material, the overcoat applied to the surface (the surface not in contact with the container) of the packaging material (P) must be taken into consideration. This overcoat is usually coated with a (meth)acrylic acid ester resin, but since the (meth)acrylic acid ester resin has resistance to alkaline water, it may not be removed in the above-mentioned printing ink stripping treatment (a). In addition, since the (meth)acrylic acid ester resin is incompatible with the resin that is the main component of the packaging material (P), the transparency of the obtained heat-shrinkable film tends to be low depending on the content of the (meth)acrylic acid ester resin. Therefore, the content of the (meth)acrylic acid ester resin must be taken into consideration in the resin composition (Z1).
[0049] Therefore, the content of the (meth)acrylic acid ester resin in the resin composition (Z1) is preferably 0.7 mass% or less, more preferably 0.6 mass% or less, and even more preferably 0.5 mass% or less. The lower the content of the (meth)acrylic acid ester resin, the better. By making the content of the (meth)acrylic acid ester resin equal to or less than the above-mentioned value, the transparency of the heat-shrinkable film tends to be maintained. In addition, if the content of the (meth)acrylic acid ester resin exceeds the above-mentioned value, the transparency of the obtained heat-shrinkable film tends to decrease. This is because the average refractive index of the (meth)acrylic acid ester resin is about 1.490 to 1.500, and because the resin that is the main component of the resin composition (Z1) and the (meth)acrylic acid ester resin are incompatible when melt-kneaded, causing scattering at the interface between them.
[0050] In addition, the content of the (meth)acrylic acid ester-based resin contained in the packaging material (P) is often variable because the type and amount of application vary depending on the design of the packaging material (P). Therefore, it is necessary to measure the content of the (meth)acrylic acid ester-based resin contained in at least one of the fluff (Pf) and the repellet (Pr) and adjust the amount of at least one of the fluff (Pf) and the repellet (Pr) added so that the (meth)acrylic acid ester-based resin contained in the resin composition (Z1) falls within the above-mentioned range.
[0051] Therefore, the content of at least one of the fluff (Pf) and the repellet (Pr) in the resin composition (Z1) is preferably 10% by mass or more and 90% by mass or less, more preferably 15% by mass or more and 80% by mass or less, and even more preferably 20% by mass or more and 70% by mass or less. When the content of at least one of the fluff (Pf) and the repellet (Pr) is equal to or more than the above numerical value, the recyclability of the circular economy tends to be improved. In addition, when the content is equal to or less than the above numerical value, the content of the (meth)acrylic acid ester resin tends to be easily adjusted to the above-mentioned range.
[0052] In the first aspect of the present invention, examples of the resin constituting the resin composition (Z1) as a main component include polystyrene resins, polyester resins, polyvinyl chloride resins, polyolefin resins, etc. These may be used alone or in combination of two or more. Among them, in the first aspect, it is preferable that the resin composition (Z1) is a resin composition mainly composed of a polyester resin (A).
[0053] In the second and third aspects of the present invention, the resin composition (Z1) contains a polyester resin (A) as a main component.
[0054] [Polyester resin (A)] The polyester resin (A) used in the first to third aspects of the present invention is not particularly limited in type as long as it is a resin having an ester bond in the main chain. Examples of the polyester resin (A) include polyester resins derived from dicarboxylic acid residues and diol residues, such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polytrimethylene terephthalate, poly-1,4-cyclohexylene dimethylene terephthalate, polyethylene succinate, and polybutylene succinate, polyester resins obtained by polymerizing monomers having carboxylic acid residues and alcohol residues in one molecule, such as polylactic acid and poly-ε-caprolactam, and copolymers thereof. One of these polyester resins (A) may be used alone, or two or more of the polyester resins (A) may be used. When the polyester resin (A) is composed of two or more kinds, the total of the two becomes the mass of the polyester resin (A), and the mass ratio of the polyester resin (A) in the resin composition (Z1) is calculated.
[0055] The polyester resin (A) used in the first to third aspects of the present invention is preferably a polyester resin derived from a dicarboxylic acid residue and a diol residue.
[0056] The polyester resin (A) used in the first to third aspects of the present invention is preferably a copolymer polyester resin, that is, at least one of the dicarboxylic acid residue and the diol residue, which are polymerization components of the polyester resin (A), is preferably a mixture of two or more types of residues. When the polyester resin (A) is composed of two or more kinds of dicarboxylic acid residues, the dicarboxylic acid residue that occupies the largest mol % relative to 100 mol % of all dicarboxylic acid residues is referred to as the first dicarboxylic acid residue, followed by the second dicarboxylic acid residue, the third dicarboxylic acid residue, ... in descending order of mol % (hereinafter, these are collectively referred to as the second or subsequent dicarboxylic acid residues). Similarly, when the polyester resin (A) is composed of two or more kinds of diol residues, the diol residue that occupies the largest mol % relative to 100 mol % of all diol residues is referred to as the first diol residue, followed by the second diol residue, the third diol residue, ... in descending order of mol % (hereinafter, these are collectively referred to as the second or subsequent diol residues). In the polyester-based resin (A), at least one of the dicarboxylic acid residue and the diol residue is composed of two or more types of residues, so that the crystallinity of the polyester-based resin (A) can be reduced, and therefore the progress of crystallization of the heat-shrinkable film tends to be inhibited, and sufficient heat-shrinkage properties can be imparted.
[0057] Examples of the dicarboxylic acid residue include aromatic dicarboxylic acid residues such as terephthalic acid, isophthalic acid, furandicarboxylic acid, 2-chloroterephthalic acid, 2,5-dichloroterephthalic acid, 2-methylterephthalic acid, 4,4-stilbene dicarboxylic acid, 4,4-biphenyl dicarboxylic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, bisbenzoic acid, bis(p-carboxyphenyl)methane, anthracene dicarboxylic acid, 4,4-diphenyl ether dicarboxylic acid, 4,4-diphenoxyethane dicarboxylic acid, 5-Na sulfoisophthalic acid, and ethylene-bis-p-benzoic acid; aliphatic dicarboxylic acid residues such as dimer acid, hydrogenated dimer acid, adipic acid, sebacic acid, succinic acid, azelaic acid, dodecanedioic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; and residues derived from ester derivatives thereof. These dicarboxylic acid residues may be contained alone or in combination of two or more.
[0058] The polyester resin (A) used in the first to third aspects of the present invention preferably contains a terephthalic acid residue as the first dicarboxylic acid residue, and preferably contains at least one residue selected from the group consisting of isophthalic acid, furandicarboxylic acid, dimer acid, hydrogenated dimer acid, 1,4-cyclohexanedicarboxylic acid, and adipic acid as the second or subsequent dicarboxylic acid residue, and more preferably contains an isophthalic acid residue as the second or subsequent dicarboxylic acid residue.
[0059] When the polyester resin (A) is composed of two or more kinds of dicarboxylic acid residues, the total content of the second or lower dicarboxylic acid residues is preferably 1 mol% or more and 40 mol% or less, more preferably 5 mol% or more and 35 mol% or less, based on 100 mol% of all dicarboxylic acid residues. If the total content of the second or lower dicarboxylic acid residues is above the above numerical value, the crystallization degree of the obtained polyester resin (A) can be kept low, and the shrinkability of the heat shrinkable film tends to be improved. In addition, if the total content of the second or lower dicarboxylic acid residues is below the above numerical value, the heat resistance of the polyester resin (A) tends not to be impaired.
[0060] Examples of the diol residue include ethylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, diethylene glycol, polytetramethylene glycol, 1,4-cyclohexanedimethanol, spiroglycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, isosorbide, etc. These diol residues may be used alone or in combination of two or more.
[0061] When the polyester resin (A) is composed of two or more kinds of diol residues, the total content of the secondary or lower diol residues is preferably 1 mol% to 45 mol%, more preferably 10 mol% to 40 mol%, based on 100 mol% of all diol residues. If the total content of the secondary or lower diol residues is above the above value, the crystallinity of the resulting polyester resin (A) can be kept low, and the shrinkability and break resistance of the heat shrinkable film tend to be improved. In addition, if the total content of the secondary or lower diol residues is below the above value, the heat resistance and chemical resistance of the polyester resin (A) tend not to be impaired.
[0062] The polyester resin (A) used in the first aspect of the present invention preferably contains an ethylene glycol residue or a 1,4-butanediol residue as the first diol residue, and more preferably contains an ethylene glycol residue as the first diol residue. The second or lower diol residue preferably contains at least one residue selected from the group consisting of 1,3-propanediol, 1,4-butanediol, neopentyl glycol, diethylene glycol, polytetramethylene glycol, 1,4-cyclohexanedimethanol, spiroglycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and isosorbide, more preferably contains at least one residue selected from 1,4-cyclohexanedimethanol residue, neopentyl glycol residue, 1,4-butanediol residue, and diethylene glycol residue, further preferably contains at least one of 1,4-cyclohexanedimethanol residue and neopentyl glycol residue as an essential component, and particularly preferably contains 1,4-cyclohexanedimethanol residue and neopentyl glycol residue as an essential component.
[0063] The polyester resin (A) used in the second aspect of the present invention preferably contains an ethylene glycol residue or a 1,4-butanediol residue as the first diol residue, and more preferably contains an ethylene glycol residue as the first diol residue. The second or lower diol residue contains a neopentyl glycol residue from the viewpoint of hand-cutting property. Also, from the viewpoint of hand-cutting property, the second or lower diol residue preferably contains a 1,4-cyclohexanedimethanol residue and a neopentyl glycol residue.
[0064] The polyester resin (A) used in the third aspect of the present invention preferably contains an ethylene glycol residue or a 1,4-butanediol residue as the first diol residue, and more preferably contains an ethylene glycol residue as the first diol residue. The second or lower diol residue contains a neopentyl glycol residue from the viewpoint of hand-cutting property. Also, from the viewpoint of hand-cutting property, the second or lower diol residue preferably contains a 1,4-cyclohexanedimethanol residue and a neopentyl glycol residue.
[0065] In the present invention, as described above, the polyester resin (A) may be used alone or two or more kinds of polyester resins (A) may be used. When the polyester resin (A) is composed of two or more kinds, the total is the mass of the polyester resin (A), and the mass ratio of the polyester resin (A) in the resin composition (Z1) is calculated. In addition, when the polyester resin (A) is contained in at least one of the fluff (Pf) and the repellet (Pr), the mass of the polyester resin (A) also includes these amounts.
[0066] When the total amount of the polyester resins (A) is taken as 100% by mass, the polyester resin (hereinafter referred to as "PET resin") containing terephthalic acid residue as the first dicarboxylic acid residue and ethylene glycol residue as the first diol residue is preferably contained in an amount of 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The upper limit of the amount of the PET resin is usually 100% by mass. When the polyester resin (A) contains the PET resin in an amount equal to or greater than the above numerical value, it tends to be possible to impart suitable shrinkage properties as a heat shrinkable film. The PET resin may be used alone or in combination of two or more kinds. When the PET resin is composed of two or more kinds, the total of the PET resins is the mass of the PET resin, and the mass ratio of the PET resin in the polyester resin (A) is calculated.
[0067] Commercially available examples of the PET-based resin include "PETGcopolyester" (manufactured by Eastman Chemical Company), "Embrace" (manufactured by Eastman Chemical Company), and "PETG KYGREEN" (manufactured by SK Chemical Company).
[0068] When the total amount of the polyester-based resins (A) is 100% by mass, the polyester-based resin (hereinafter referred to as "PBT-based resin") containing a terephthalic acid residue as the first dicarboxylic acid residue and a 1,4-butanediol residue as the first diol residue preferably accounts for 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. By containing the PBT resin in the polyester resin (A) in an amount not more than the above numerical value, the heat resistance of the heat shrinkable film tends to be improved and the heat shrink behavior tends to be adjusted. That is, since the glass transition temperature (Tg) of the PET resin and the Tg of the PBT resin are significantly different, the Tg of the resin composition (Z1) can be shifted by melt-kneading the two compatible resins, so that the temperature at which heat shrinkage starts can be adjusted and rapid shrinkage from the start of heat shrinkage tends to be suppressed. On the other hand, if the polyester resin (A) contains the PBT resin in an amount exceeding the above-mentioned value, the Tg of the polyester resin (A) is lowered to a temperature relatively close to room temperature, so that the dimensions tend to change during storage before use as a packaging material. Also, crystallization is promoted, so that it tends to be difficult to obtain the heat shrinkage required for the heat shrinkable film. The PBT resin may be used alone or in combination of two or more kinds. When the PBT resin is composed of two or more kinds, the total of the PBT resins is the mass of the PBT resin, and the mass ratio of the PBT resin in the polyester resin (A) is calculated.
[0069] Commercially available examples of the PBT resin include "Novaduran" (manufactured by Mitsubishi Engineering Plastics Corporation) and "Trecon" (manufactured by Toray Industries, Inc.).
[0070] The above resins (PET resin, PBT resin, etc.) that can be preferably used as the polyester resin (A) and their preferred contents are shown, but since the polyester resin (A) undergoes an ester exchange reaction in a molten state during molding, when two or more polyester resins (A) are used, it may be difficult to identify the content ratio of each resin or to distinguish whether it is a mixture or a copolymer. Therefore, when the resin composition (Z1) is a resin composition mainly composed of the polyester resin (A), the properties as a heat-shrinkable film can be examined by the type of residue contained in the resin composition (Z1) and the content of the residue.
[0071] That is, in the present invention, the terephthalic acid residue is preferably contained in 75 mol% or more, more preferably 80 mol% or more, and even more preferably 85 mol% or more, based on 100 mol% of all dicarboxylic acid residues contained in the resin composition (Z1). The upper limit is usually 100 mol%. By containing the terephthalic acid residue in the above-mentioned amount or more, it tends to be possible to maintain the heat resistance and rigidity required for the heat shrinkable film.
[0072] In the present invention, the ethylene glycol residue is preferably contained in an amount of 50 mol% to 90 mol%, more preferably 55 mol% to 85 mol%, and even more preferably 60 mol% to 80 mol%, based on 100 mol% of all diol residues contained in the resin composition (Z1). By containing ethylene glycol residues within the above numerical range, it tends to be possible to maintain the heat resistance and chemical resistance required for the heat shrinkable film.
[0073] In the present invention, the resin composition (Z1) preferably contains at least one selected from 1,4-cyclohexanedimethanol residues, neopentyl glycol residues, 1,4-butanediol residues, and diethylene glycol residues in an amount of 10 mol % to 50 mol %, more preferably 15 mol % to 45 mol %, and even more preferably 20 mol % to 40 mol % relative to the total diol residues contained therein (100 mol %). By containing at least one selected from 1,4-cyclohexanedimethanol residues, neopentyl glycol residues, 1,4-butanediol residues, and diethylene glycol residues within the above numerical range, the heat resistance and chemical resistance required for the heat shrinkable film tend to be maintained.
[0074] When the resin composition (Z1) contains a 1,4-cyclohexanedimethanol residue, the 1,4-cyclohexanedimethanol residue is preferably contained in an amount of 1 mol % to 40 mol % and more preferably 5 mol % to 35 mol % relative to 100 mol % of all diol residues contained in the resin composition (Z1).
[0075] When the resin composition (Z1) contains a neopentyl glycol residue, the neopentyl glycol residue is preferably contained in an amount of 1 mol % or more and 40 mol % or less, and more preferably 2 mol % or more and 20 mol % or less, relative to 100 mol % of all diol residues contained in the resin composition (Z1).
[0076] When the resin composition (Z1) contains 1,4-butanediol residues, the amount of 1,4-butanediol residues is preferably 3 mol % or more and 25 mol % or less, and more preferably 6 mol % or more and 20 mol % or less, relative to 100 mol % of all diol residues contained in the resin composition (Z1).
[0077] When the resin composition (Z1) contains a diethylene glycol residue, the diethylene glycol residue is preferably contained in an amount of 0.5 mol % or more and 7 mol % or less, and more preferably 1 mol % or more and 6 mol % or less, relative to 100 mol % of all diol residues contained in the resin composition (Z1).
[0078] (Other Ingredients) The resin composition (Z1) may contain resins other than the polystyrene-based resins, polyester-based resins, polyvinyl chloride-based resins, and polyolefin-based resins. Examples of other resins include polycarbonate-based resins, polyamide-based resins, fluorine-based resins, polyvinyl alcohol-based resins, polyacrylonitrile-based resins, polyether-based resins, cellulose-based resins, polyimide-based resins, polyurethane-based resins, polyphenylene sulfide-based resins, polyphenylene ether-based resins, polyvinyl acetal-based resins, polyamideimide-based resins, polyamide bismaleimide-based resins, polyarylate-based resins, polyetherimide-based resins, polyetheretherketone-based resins, polyetherketone-based resins, polyethersulfone-based resins, polyketone-based resins, polyacetal-based resins, polysulfone-based resins, aramid-based resins, etc. These may be used alone or in combination of two or more.
[0079] The resin composition (Z1) may also contain a thermoplastic elastomer. Examples of the thermoplastic elastomer that may be contained include styrene-based thermoplastic elastomers, amide-based thermoplastic elastomers, olefin-based thermoplastic elastomers, urethane-based thermoplastic elastomers, vinyl chloride-based thermoplastic elastomers, acrylic-based thermoplastic elastomers, fluorine-based thermoplastic elastomers, silicone-based thermoplastic elastomers, ionomers, and their blends, alloys, modified products, dynamically crosslinked products, block copolymers, graft copolymers, random copolymers, and core-shell type multilayer rubbers. These may be used alone or in combination of two or more. However, since ester-based thermoplastic elastomers have ester bonds in the main chain, they are included in the polyester resin (A).
[0080] In addition, the resin composition (Z1) may be appropriately added with additives generally blended in resin compositions within the range that does not significantly impair the effects of the present invention. Examples of the additives include recycled resins (fluff or repellets of heat-shrinkable films without printing) generated from trimming losses such as edges, which are added for the purpose of improving and adjusting the molding processability, productivity, and various physical properties of the heat-shrinkable film, inorganic particles such as silica, talc, kaolin, and calcium carbonate, pigments such as titanium oxide and carbon black, flame retardants, weather resistance stabilizers, heat resistance stabilizers, antistatic agents, melt viscosity improvers, crosslinking agents, lubricants, nucleating agents, plasticizers, antioxidants, antioxidants, light stabilizers, ultraviolet absorbers, neutralizers, antifogging agents, antiblocking agents, slip agents, and colorants. These may be used alone or in combination of two or more.
[0081] [Method for producing heat shrinkable film] The heat shrinkable film of the present invention can be produced by a conventionally known production method using the resin composition (Z1). The shape of the heat shrinkable film of the present invention is not particularly limited, and may be either planar or tubular, but is preferably planar in terms of productivity (several pieces can be produced in the width direction of the raw film) and ease of printing.
[0082] Examples of the method for producing the flat film include a method for producing a flat heat-shrinkable film by melting the resin composition (Z1) using an extruder, extruding the molten resin into a flat shape from a die such as a T-die, and cooling and solidifying the extruded resin with a cooling roll to obtain an unstretched film, stretching the unstretched film in at least one direction, and then annealing, cooling, and optionally subjecting the film to a corona discharge treatment or the like.
[0083] Alternatively, the resin composition (Z1) is melted using an extruder, the molten resin is extruded into a tube shape from a die or the like, and the extruded molten resin is cooled and solidified using an air or water cooler to obtain an unstretched film. Then, the tube is stretched in at least one direction by applying internal pressure to the tube in a heated tunnel furnace by the tubular method, so as to inflate the tube like a balloon, and then the annealed and cooled tubular stretched film is cut open to produce a flat film.
[0084] The heat-shrinkable films according to the first to third aspects of the present invention need only have at least one layer (I) made of a resin composition (Z1) containing at least one of fluff (Pf) and repellets (Pr) obtained using a packaging material (P) as a starting material. Therefore, a laminate film having the layer (I) and other layers can also be produced in the same manner, for example, by co-extrusion using multiple extruders.
[0085] Examples of the stretching method include a method of stretching in at least one direction by a roll stretching method, a tenter stretching method, a tubular stretching method, a long distance stretching method, etc. Stretching can also be performed by a combination of these stretching methods, and the film may be stretched only in the longitudinal direction, or only in the transverse direction, or may be stretched in the longitudinal direction and then in the transverse direction, or may be stretched in the transverse direction and then in the longitudinal direction. Stretching may also be performed two or more times in the same direction. Furthermore, the film may be stretched in the longitudinal direction, then in the transverse direction, and then in the longitudinal direction. Stretching may also be performed simultaneously in the longitudinal and transverse directions by a simultaneous biaxial stretching machine. A tubular unstretched film may also be radially stretched by internal pressure by tubular molding.
[0086] The stretching temperature needs to be changed depending on the softening temperature of the resin constituting the heat-shrinkable film and the shrinkage characteristics required of the heat-shrinkable film, but is preferably 60°C or higher and 130°C or lower, more preferably 70°C or higher and 120°C or lower, and even more preferably 80°C or higher and 110°C or lower.
[0087] In addition, the stretching ratio needs to be changed depending on the constituent components of the heat-shrinkable film, the stretching method, the stretching temperature, the desired heat shrinkage rate, etc., but the stretching ratio in the main shrinkage direction is preferably 2 to 8 times, more preferably 3 to 7 times, and even more preferably 4 to 6 times.
[0088] When the heat shrinkable film of the present invention is used for applications such as overlapping containers and trays, it is preferably stretched in the longitudinal and transverse directions. In this case, the main shrinkage direction may be either the longitudinal or transverse direction. When the film is used for applications requiring shrinkage properties in approximately one direction, such as labels attached to food containers and beverage containers, it is preferably stretched uniaxially in the main shrinkage direction, but stretching at a stretch ratio of 1.03 to 1.5 times in the direction perpendicular to the main shrinkage direction is also effective in imparting good shrinkage properties. In the heat shrinkable film of the present invention, it is preferable that the main shrinkage direction is the transverse direction (TD) and the direction perpendicular to the main shrinkage direction is the machine direction (MD).
[0089] After stretching, the heat-shrinkable film may be heat-treated or relaxed at a temperature of 50° C. to 120° C. as needed to adjust the heat shrinkage rate and various physical properties of the heat-shrinkable film. After stretching, heat-treatment, or relaxation, the film may be quickly cooled within a time period during which the molecular orientation is not relaxed, thereby imparting shrinkage properties to the heat-shrinkable film. The cooled heat-shrinkable film may then have its edges trimmed and be wound around a core using a winder or the like to form a film roll.
[0090] [Layer structure of heat shrinkable film] The heat shrinkable film according to the first to third aspects of the present invention may have at least one layer (I) made of a resin composition (Z1) containing at least one of fluff (Pf) and pellets (Pr) obtained from a packaging material (P) as a starting material. Therefore, the heat shrinkable film of the present invention may be a single layer film of the layer (I), or may be a film in which the layer (I) and other layers are laminated. In addition, the layer structure is not particularly limited. In particular, the heat-shrinkable films according to the first to third aspects of the present invention preferably comprise at least two layers, namely, a layer (II) made of a resin composition (Z2) that does not contain a raw material made of the packaging material (P), and the layer (I).
[0091] Examples of the resin constituting the resin composition (Z2) as a main component include polystyrene-based resins, polyester-based resins, polyvinyl chloride-based resins, polyolefin-based resins, etc. Among them, in the present invention, it is preferable that the resin composition (Z2) is a resin composition mainly composed of the polyester-based resin (A).
[0092] From the viewpoint of hand cuttability, the polyester resin (A) contained in the resin composition (Z2) preferably contains at least one of a 1,4-cyclohexanedimethanol residue and a neopentyl glycol residue as a diol residue.
[0093] When the heat-shrinkable film according to the first to third aspects of the present invention is a heat-shrinkable film consisting of at least two layers, namely, the layer (I) and a layer (II) consisting of the resin composition (Z2), suitable lamination structures include, for example, a two-layer structure consisting of "layer (I) / layer (II)", a two-kind three-layer structure consisting of "layer (I) / layer (II) / layer (I)" or "layer (II) / layer (I) / layer (II)", a three-kind three-layer structure consisting of "layer (I) / layer (II) / layer (III)", "layer (II) / layer (I) / layer (III)", and "layer (I) / layer (III) / layer (II)" in which another layer (III) is further laminated, and a three-kind three-layer structure consisting of "layer (I) / layer (II) / layer (III)", "layer (II) / layer (I) / layer (III)", and "layer (I) / layer (III) / layer (II)", A three-kind four-layer structure consisting of "layer (II) / layer (III)", "layer (III) / layer (I) / layer (III) / layer (II)", "layer (III) / layer (I) / layer (II) / layer (III)", "layer (I) / layer (III) / layer (II) / layer (III) / layer (I)", "layer (II) / layer (III) / layer (I) / layer (III) / layer (II)", "layer (III) / layer (II) / layer (I) / layer (II) / layer (III)", "layer (III) / layer (II) / layer (I) / layer (II) / layer (III)", "layer (III) / layer (I) / layer (II) / layer (I) / layer (III)", and a three-kind five-layer structure consisting of "layer (I) / layer (III) / layer (II) / layer (III) / layer (II) / layer (I) / layer (III)" can be adopted, and there is no particular limitation on the number of layers or the type of the other layer (III) mentioned above. Furthermore, other layers, such as layers made of nonwoven fabric, paper, metal, etc., may be laminated as the layer (III). The layers may be laminated by coextrusion, or films obtained in separate processes may be laminated by pressing or laminating.
[0094] When the heat-shrinkable film according to the first to third aspects of the present invention is a heat-shrinkable film consisting of at least two layers, namely, the layer (I) and a layer (II) consisting of the resin composition (Z2), it is preferable that the heat-shrinkable film has a two-kind three-layer structure consisting of "layer (II) / layer (I) / layer (II)". Since the layer (II) does not contain the raw material consisting of the packaging material (P), by adopting a two-kind three-layer structure consisting of "layer (II) / layer (I) / layer (II)", it is possible to maintain surface properties such as gloss, slipperiness, and printing properties at the same level as conventional heat-shrinkable films.
[0095] Whether the heat-shrinkable film of the present invention is a single-layer film of the layer (I) or a laminate film consisting of at least two layers, that is, the layer (I) and the layer (II), it is preferable to add an antiblocking agent to the layer forming the surface layer in order to impart slip properties to the film and prevent blocking.
[0096] Examples of the antiblocking agent include inorganic particles such as silica, talc, and calcium carbonate, inorganic oxides, carbonates, and organic particles such as crosslinked acrylic, crosslinked polyester, crosslinked polystyrene, and silicone. Organic particles having a multilayer structure formed by multistage polymerization can also be used. These may be used alone or in combination of two or more. Among them, silica and organic particles are preferred.
[0097] The antiblocking agent roughens the film surface to exhibit slipperiness and blocking resistance, and therefore, unless an appropriate amount and type are selected, the transparency and gloss of the film are impaired. Therefore, the amount of the antiblocking agent added is preferably 0.01% by mass or more and 2% by mass or less, more preferably 0.015% by mass or more and 1.5% by mass or less, and even more preferably 0.02% by mass or more and 1% by mass or less, based on the mass of the entire resin composition constituting the layer forming the surface layer (100% by mass). If the amount of the antiblocking agent added is too small, the antiblocking agent is difficult to precipitate on the film surface, and it is difficult to form unevenness on the film surface, so that sufficient slipperiness and blocking resistance tend to be difficult to exhibit. On the other hand, if the amount is too large, excessive unevenness on the film surface tends to occur, which tends to inhibit transparency due to surface roughness and to cause winding distortion of the film roll due to excessive slipperiness.
[0098] The shape of the antiblocking agent is not particularly limited, but from the viewpoints of suppressing aggregation, uniform dispersion, suppressing diffuse reflection of transmitted light, and unevenness formed on the film surface, spherical ones are preferably used. The particle size of the antiblocking agent is preferably 0.5 μm to 10 μm, more preferably 1 μm to 8 μm, and even more preferably 1 μm to 6 μm. If the particle size of the antiblocking agent is too small, it is difficult to deposit on the surface, and even the antiblocking agent deposited on the surface tends to be difficult to impart sufficient unevenness to exhibit slip properties and blocking resistance. On the other hand, if the particle size of the antiblocking agent is too large, when the heat shrinkable film of the present invention is printed to enhance the design, ink loss and the like tend to occur, which tends to impair the appearance of the printed pattern. The particle size distribution of the antiblocking agent is not particularly limited, but a narrow particle size distribution is preferable in view of the adverse effects due to the size of the particle size. If the particle size distribution is too wide, it is possible that particles deviating from the above-mentioned range of particle sizes that are preferably used will be included.
[0099] The total thickness of the heat-shrinkable film of the present invention is not particularly limited, but from the viewpoint of application to packaging materials, it is preferably 5 μm or more and 200 μm or less, more preferably 10 μm or more and 150 μm or less, and even more preferably 15 μm or more and 70 μm or less.
[0100] When the heat-shrinkable film of the present invention is a heat-shrinkable film consisting of at least two layers, the layer (I) and a layer (II) consisting of a resin composition (Z2), the thickness of each layer and the lamination ratio are not particularly limited, but from the viewpoint of improving recyclability in a circular economy, the ratio of the layer thickness of the layer (I) to the total layer thickness is preferably 50% to 99%, more preferably 55% to 95%, and even more preferably 60% to 90%. Here, the layer thickness of the layer (I) refers to the total thickness of the layer (I) when the layer (I) is present in a plurality of layers, such as in a "layer (I) / layer (II) / layer (I)" configuration.
[0101] In addition, when the heat-shrinkable film of the present invention is composed of at least two layers, the layer (I) and the layer (II), it is preferable that the layer (I) and the layer (II) have a continuous layer portion in which the two layers are adjacent to each other, and that the resin constituting the layer (I) as a main component is the same as the resin constituting the layer (II) as a main component.Moreover, it is more preferable that the layer (I) and the layer (II) have a continuous layer portion in which the two layers are adjacent to each other, and that the resin composition (Z1) is a resin composition mainly composed of the polyester resin (A), and that the resin composition (Z2) is a resin composition mainly composed of the polyester resin (A). Since the layer (I) and the layer (II) have a continuous layer portion in which the two layers are adjacent to each other, and the resin constituting the layer (I) as a main component is the same as the resin constituting the layer (II) as a main component, delamination at the interface between the layer (I) and the layer (II) tends to be less likely to occur.
[0102] On the other hand, in the analysis of an unknown heat-shrinkable film, if the film has a continuous layer portion in which layers (I) and (II) are adjacent to each other, and the resin constituting layer (I) as a main component is the same as the resin constituting layer (II) as a main component, the interface between adjacent layers (I) and (II) may not be clearly distinguishable. Here, the fact that the interface between adjacent layers (I) and (II) is not clearly distinguishable refers to a state in which, when a cross-section of the heat-shrinkable film is observed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM), there is no contrast between adjacent layers (I) and (II) and the interface cannot be determined. Therefore, in analyzing an unknown heat-shrinkable film to determine whether it is within the technical scope of the present invention, if the film has a continuous layer portion consisting of two adjacent layers, layer (I) and layer (II), and the resin constituting layer (I) as a main component is the same as the resin constituting layer (II) as a main component, and the interface between adjacent layers (I) and (II) cannot be clearly distinguished, it is permissible to judge that layers (I) and (II) are combined as a single layer.
[0103] In addition, the heat-shrinkable film of the present invention can be subjected to surface treatments or finishes such as slitting, corona treatment, printing, application of adhesive, coating, vapor deposition, etc., as well as bag making processing using various solvents or heat sealing, and perforation processing, if necessary.
[0104] (transparency) It is important to evaluate the transparency of the heat shrinkable film according to the first and second aspects of the present invention by the light transmittance in the spectrophotometric measurement according to JIS K0115 (2004). This is because the heat shrinkable film according to the first and second aspects contains at least one of fluff (Pf) and repellet (Pr) obtained from the packaging material (P) as a starting material, and therefore it is necessary to suppress the influence of the printing ink applied to the packaging material (P). However, printing is applied in a wide variety of colors. In other words, it is most important in the present invention that the appearance and transparency of the obtained heat shrinkable film are not impaired regardless of the color of the packaging material (P) printed thereon that is used as the starting material. Therefore, it is important that the heat shrinkable films according to the first and second aspects of the present invention have a light transmittance of 85% or more at a measurement wavelength of 400 nm in spectrophotometric measurement in accordance with JIS K0115 (2004). If the light transmittance of a heat-shrinkable film in spectrophotometric measurement is less than 85% at a measurement wavelength of 400 nm, the heat-shrinkable film will absorb purple light and become reddish, which will impair the appearance of the heat-shrinkable film.
[0105] Furthermore, the heat shrinkable film according to the third aspect of the present invention preferably has a light transmittance of 85% or more at a measurement wavelength of 400 nm in spectrophotometric measurement in accordance with JIS K0115 (2004). If the light transmittance of a heat-shrinkable film in spectrophotometric measurement is less than 85% at a measurement wavelength of 400 nm, the heat-shrinkable film will absorb purple light and become reddish, which tends to impair the appearance of the heat-shrinkable film.
[0106] Furthermore, the heat shrinkable films according to the first to third aspects of the present invention preferably have a light transmittance of 85% or more at any measured wavelength of 400 nm or more and 800 nm or less. If the light transmittance is 85% or more at any measured wavelength of 400 nm or more and 800 nm or less, the heat shrinkable film tends to have a better appearance. For example, if the light transmittance is less than 85% in the range of 700 nm to 800 nm, the heat shrinkable film tends to absorb red light and become a bluish film, impairing the appearance.
[0107] The transparency of the heat shrinkable films according to the first to third aspects of the present invention is also evaluated by the total light transmittance measured in accordance with JIS K7361-1 (1997) and the haze value measured in accordance with JIS K77136 (2000). The haze value is defined as the ratio of the diffuse transmittance to the total light transmittance.
[0108] The heat shrinkable films according to the first to third aspects of the present invention preferably have a total light transmittance of 87.5% or more, more preferably 88.0% or more, and even more preferably 88.5% or more. If the total light transmittance is equal to or more than the above values, the transparency of the heat shrinkable film is high, and the visibility of the container and the backside print tends to be improved.
[0109] The heat shrinkable films according to the first to third aspects of the present invention preferably have a haze value of 10% or less, more preferably 9% or less, and even more preferably 8% or less. If the haze value is less than the above range, the heat shrinkable film tends to scatter less, and the visibility of the contents and the backside print tends to be improved.
[0110] The heat shrinkable films according to the first to third aspects of the present invention are also preferably evaluated by a yellowness index (YI) measured in accordance with JIS K7373 (2006). The heat shrinkable film of the present invention preferably has a yellowness index (YI) of -5 or more and 5 or less, more preferably -3 or more and 3 or less. When the yellowness index (YI) is within the above range, there is a tendency that the appearance of the heat shrinkable film is less hindered by the color.
[0111] (Heat shrinkage rate of heat shrinkable film) The heat shrinkable films according to the first to third aspects of the present invention preferably have a heat shrinkage rate in the main shrinkage direction of 30% or more when immersed in hot water at 100° C. for 10 seconds, more preferably 40% to 90%, and even more preferably 50% to 80%. In general, a heat-shrinkable film is used to cover an object to be covered, such as a container, and then passed through an atmosphere heated by a heater, hot air, water vapor, etc. for a relatively short time (several seconds to a dozen seconds) to shrink the heat-shrinkable film and attach it to the object to be covered. Therefore, the heat shrinkage rate of a heat-shrinkable film is an index for determining the adhesion to the object to be covered and the shape-following ability. Therefore, if the heat shrinkage rate in the main shrinkage direction when immersed in 100°C warm water for 10 seconds is equal to or greater than the above value, it can be determined that the heat shrinkable film can be adequately attached to the object to be covered within the shrink processing time.
[0112] Furthermore, the heat shrinkage rate in the main shrinkage direction when immersed in 90°C warm water for 10 seconds is preferably 20% or more, more preferably 25% or more and 80% or less, and even more preferably 30% or more and 75% or less. Furthermore, the heat shrinkage rate in the main shrinkage direction when immersed in 80°C warm water for 10 seconds is preferably 15% or more, more preferably 20% or more and 70% or less, and more preferably 25% or more and 60% or less. In addition, the heat shrinkage rate in the main shrinkage direction when immersed in 70°C warm water for 10 seconds is preferably 5% or more, more preferably 6% or more and 60% or less, and more preferably 8% or more and 55% or less. In the shrinking step, the heat-shrinkable film may be slightly shrunk (pre-shrunk) at a low temperature to fix the film in position on the object to be covered before completely covering the object to be covered. In this case, if the heat shrinkage rate at each temperature is within the above-mentioned preferred range, the film tends to be able to be shrunk gradually on the object to be covered from a lower temperature.
[0113] Furthermore, the thermal shrinkage rate when immersed in 50°C warm water for 10 seconds is preferably 5% or less, more preferably 3% or less, even more preferably 1% or less, and most preferably 0%, in both the main shrinkage direction and the direction perpendicular to the main shrinkage direction. If the thermal shrinkage rate when immersed in 50°C warm water for 10 seconds is greater than the above value, the film is likely to have a large natural shrinkage rate, which tends to cause poor appearance such as tightness when rolled up and stored or uneven roll end surfaces.
[0114] Furthermore, when used for applications requiring shrinkage properties in approximately one direction, such as labels attached to food containers or beverage containers, the heat shrinkage rate in the direction perpendicular to the main shrinkage direction when immersed in hot water at 100° C. for 10 seconds is preferably −5% or more and 15% or less, more preferably −5% or more and 10% or less. A negative value for the heat shrinkage rate indicates that the film expands in that direction. By having the heat shrinkage rate in the direction perpendicular to the main shrinkage direction when immersed in 100°C warm water for 10 seconds within the above range, there is a tendency that distortion of characters or patterns printed on the heat shrinkable film can be suppressed when the film is attached to an object to be covered. In addition, by expanding or contracting in the direction perpendicular to the main shrinkage direction, an ironing effect that alleviates wrinkles that occur when the film is attached is achieved, which is preferable.
[0115] Furthermore, when used for applications requiring shrinkage properties in approximately one direction, such as labels attached to food containers or beverage containers, the heat shrinkage rate in the direction perpendicular to the main shrinkage direction when immersed in warm water at 70°C to 90°C for 10 seconds is preferably -5% or more and 10% or less, and more preferably -5% or more and 7% or less. By having a thermal shrinkage rate in the direction perpendicular to the main shrinkage direction when immersed in warm water at 70°C to 90°C for 10 seconds within the above range, it is possible to suppress distortion of characters or patterns printed on the heat-shrinkable film when the film is attached to an object to be covered. Also, it is possible to suppress deviation of the fixing position when fixing the position by pre-shrinking.
[0116] (tensile modulus) From the viewpoint of the stiffness (rigidity at room temperature) of the film, the heat shrinkable film according to the first to third aspects of the present invention preferably has a tensile modulus of 1500 MPa or more, more preferably 1600 MPa or more, and even more preferably 1700 MPa or more in an atmospheric temperature of 23° C. in a direction perpendicular to the main shrinkage direction (hereinafter also referred to as the "perpendicular direction"). The upper limit of the tensile modulus in the perpendicular direction is not particularly limited, but considering the upper limit of the tensile modulus of a heat shrinkable film that is usually used, the upper limit is preferably 4000 MPa or less. If the tensile modulus in the perpendicular direction is the above-mentioned value or more, the stiffness (rigidity at room temperature) of the film as a whole is high, and even when the thickness of the film is reduced, the heat shrinkable film is less likely to break when the heat shrinkable film is applied to a container using a labeling machine or the like.
[0117] The tensile modulus of elasticity in the main shrinkage direction of the heat shrinkable film according to the first aspect of the present invention at an ambient temperature of 23° C. is preferably 5500 MPa or less, more preferably 4750 MPa or less, and even more preferably 4000 MPa or less, for commonly used heat shrinkable films. By setting the tensile modulus of elasticity in the main shrinkage direction to the above-mentioned value or less, the difference between the tensile modulus of elasticity in the main shrinkage direction and the orthogonal direction can be suppressed, and hand-tearability tends to be ensured.
[0118] The heat shrinkable film according to the second aspect of the present invention preferably has a tensile modulus in the main shrinkage direction at an ambient temperature of 23° C. of 4000 MPa or less, more preferably 3950 MPa or less, and even more preferably 3900 MPa or less. By setting the tensile modulus in the main shrinkage direction to the above-mentioned value or less, it is possible to prevent a cut generated in the longitudinal direction perpendicular to the main shrinkage direction of the film from propagating in the main shrinkage direction, and hand tearability tends to be improved.
[0119] Furthermore, the heat shrinkable film according to the third aspect of the present invention has a tensile modulus in the main shrinkage direction at an ambient temperature of 23° C. of 4000 MPa or less, preferably 3950 MPa or less, and more preferably 3900 MPa or less. By making the tensile modulus in the main shrinkage direction equal to or less than the above numerical value, it is possible to prevent a cut generated in the longitudinal direction perpendicular to the main shrinkage direction of the film from propagating in the main shrinkage direction, thereby improving hand tearability.
[0120] In the heat shrinkable films according to the first to third aspects of the present invention, the difference between the tensile modulus in the main shrinkage direction at an atmospheric temperature of 23° C. and the tensile modulus in the orthogonal direction at an atmospheric temperature of 23° C. (tensile modulus in the main shrinkage direction−tensile modulus in the orthogonal direction) is preferably 2000 MPa or less, more preferably 1900 MPa or less, and even more preferably 1850 MPa or less. By making the difference between the tensile modulus in the main shrinkage direction and the tensile modulus in the orthogonal direction equal to or less than the above-mentioned numerical value, it is possible to prevent a cut generated in the longitudinal direction orthogonal to the main shrinkage direction of the film from propagating in the main shrinkage direction, and hand tearability tends to be improved.
[0121] Furthermore, in the heat shrinkable films according to the first to third aspects of the present invention, the ratio of the tensile modulus in the main shrinkage direction at an atmospheric temperature of 23° C. to the tensile modulus in the orthogonal direction at an atmospheric temperature of 23° C. (tensile modulus in the main shrinkage direction / tensile modulus in the orthogonal direction) is preferably 2.0 or less, more preferably 1.9 or less, and even more preferably 1.8 or less. By setting the ratio of the tensile modulus in the main shrinkage direction to the tensile modulus in the orthogonal direction to the above-mentioned numerical value or less, it is possible to prevent a cut generated in the longitudinal direction orthogonal to the main shrinkage direction of the film from propagating in the main shrinkage direction, and hand tearability tends to be improved.
[0122] (shrinkage stress) The heat shrinkable films according to the first to third aspects of the present invention preferably have a maximum shrinkage stress in the main shrinkage direction of 10 MPa or less, preferably 9 MPa or less, more preferably 8 MPa or less, when immersed in silicone oil at 80° C. for 10 seconds. On the other hand, the lower limit of the maximum shrinkage stress in the main shrinkage direction is preferably 0.5 MPa or more, from the viewpoint of maintaining the adhesion between the object to be covered and the heat shrinkable film. If the maximum shrinkage stress in the main shrinkage direction of the film is equal to or less than the above numerical value, there is a tendency that the object to be covered is less likely to be deformed by the heat shrinkage of the heat shrinkable film.
[0123] (Tensile breaking strength) The heat shrinkable films according to the first to third aspects of the present invention preferably have a tensile breaking strength in the machine direction (MD) of 35 MPa or more, more preferably 40 MPa or more, measured in accordance with JIS K7127 under conditions of an atmospheric temperature of 23° C. and a pulling speed of 200 mm / min. When the tensile breaking strength in the machine direction (MD) is equal to or more than the above numerical value, the heat shrinkable film is less likely to break or suffer other problems during secondary processing such as a printing process.
[0124] (Tensile elongation at break) The heat shrinkable films according to the first to third aspects of the present invention preferably have a tensile elongation at break in the machine direction (MD) of 100% or more, more preferably 150% or more, and even more preferably 200% or more, measured in accordance with JIS K7127 under conditions of an atmospheric temperature of 23° C. and a pulling speed of 200 mm / min. When the tensile elongation at break in the machine direction (MD) is equal to or more than the above values, problems such as breakage of the heat shrinkable film tend to be less likely to occur during secondary processing steps such as a printing step.
[0125] [Packaging materials] The heat-shrinkable films according to the first to third aspects of the present invention can be used for various applications, but preferably, a printed layer is formed on one or both sides of the heat-shrinkable film to form packaging materials such as heat-shrinkable labels to be attached to glass containers and plastic containers such as PET bottles.
[0126] In general, a printing layer or an overcoat layer is formed on at least one of the entire surface or part of the front and back surfaces of a heat-shrinkable film used for label applications by a known method such as gravure printing, flexographic printing, offset printing, bar coater, etc. The printing ink is not particularly limited and can be appropriately selected depending on the printing method, and examples thereof include solvent-based (non-aqueous) or aqueous acrylic resin-based or urethane resin-based inks, foaming inks, heat-foaming inks, etc.
[0127] Packaging materials for labeling purposes are processed from a flat shape to a cylindrical shape or the like depending on the packaged item, and then used for packaging. For cylindrical containers such as PET bottles that require printing, first print the required image on one side of a wide flat film wound on a roll, cut it to the required width, fold it so that the printed side is on the inside, and center-seal (the shape of the sealed part is a so-called envelope seal) to form a cylindrical shape. Center-sealing methods include organic solvent sealing, heat sealing, adhesive, and impulse sealer methods, but in consideration of the appearance, it is preferable to use an organic solvent sealing method.
[0128] [Molded products, containers] The heat shrinkable films according to the first to third aspects of the present invention are excellent in film stiffness (rigidity at room temperature), shrink finish, transparency, mechanical strength, etc., and have small natural shrinkage and shrinkage stress, so that when attached to a molded product or container, they can be closely attached to the shape of even molded products or containers having complex shapes (for example, a cylinder with a narrowed center, a square prism with corners, a pentagonal prism, a hexagonal prism, etc.), and can be used as a packaging material that can be beautifully attached without wrinkles, pockmarks, etc. Therefore, examples of objects to which the heat shrinkable film of the present invention can be attached include molded products or containers of various shapes, such as PET bottles, plastic containers, metal, porcelain, glass, paper, bottles, PET bottles, trays, lunch boxes, containers for deli food, and containers for dairy products. In particular, when the heat-shrinkable film of the present invention is used as a heat-shrinkable label for a blown bottle, it is particularly advantageous in that it can adhere closely to even complex shapes, as described above, and can produce containers with beautiful labels that are free of wrinkles, pitting, etc.
[0129] Examples of materials constituting the plastic container fitted with the packaging material of the present invention include polyethylene terephthalate, polystyrene, rubber modified impact resistant polystyrene (HIPS), styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, styrene-maleic anhydride copolymer, acrylonitrile-butadiene-styrene copolymer (ABS), methacrylate-butadiene-styrene copolymer (MBS), polyvinyl chloride resin, phenol resin, urea resin, melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. These plastic containers may be a mixture or laminate of two or more resins. EXAMPLES
[0130] Examples performed to clarify the effects of the present invention will be described below. The present invention is not limited to the following examples and comparative examples. In the following examples, comparative examples, and reference examples, the flow direction of the heat shrinkable film from the extruder is indicated as (MD), and the direction perpendicular to the MD is indicated as (TD). The measured values and evaluations shown in the following Examples, Comparative Examples, and Reference Examples were carried out as follows:
[0131] (1) Light transmittance in spectrophotometric measurements The light transmittance of the obtained heat shrinkable film was measured at a measurement wavelength of 400 nm or more and 800 nm or less in accordance with JIS K0115 (2004). The measurement was performed with a measurement start wavelength of 800 nm, and the measurement wavelength was changed to a measurement end wavelength of 400 nm at a scan speed of 300 nm / min, and the light transmittance was measured at measurement wavelength intervals of 0.5 nm. At this time, the heat shrinkable film was judged as having a light transmittance of 85% or more at a measurement wavelength of 400 nm (◯), and the heat shrinkable film was judged as having a light transmittance of less than 85% at a measurement wavelength of 400 nm (×). In addition, the light transmittance at measurement wavelengths of 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, and 800 nm were extracted as representative values.
[0132] (2) Heat shrinkage rate The obtained heat shrinkable film was cut into strips with a size of 200 mm in MD and 10 mm in TD, and benchmark lines were marked at intervals of 100 mm in MD. The strips were then immersed in hot water baths set at temperatures of 100°C, 90°C, 80°C, 70°C, and 50°C for 10 seconds, and the benchmark line spacing after shrinkage was measured to measure the amount of shrinkage (= benchmark line spacing before shrinkage - benchmark line spacing after shrinkage). The thermal shrinkage rate was calculated as the ratio of the amount of shrinkage to the benchmark line spacing before shrinkage (= (amount of shrinkage / benchmark line spacing before shrinkage) x 100%). The obtained heat shrinkable film was cut into a size of 10 mm in MD and 200 mm in TD, and benchmark lines were marked at intervals of 100 mm in the TD. Then, the same measurement as for the heat shrinkage rate measurement in the MD was performed to measure the heat shrinkage rate in the TD.
[0133] (3) Tensile breaking strength, tensile breaking elongation The obtained heat-shrinkable film was cut into a size of 120 mm in MD and 15 mm in TD, and the tensile strength and tensile elongation in MD of the film were measured at an atmospheric temperature of 23°C at a pulling speed of 200 mm / min in accordance with JIS K7127, and the average values of 10 measured values were calculated. The obtained heat-shrinkable film was cut into a size of 15 mm in MD and 120 mm in TD, and the tensile strength and tensile elongation in TD of the film were measured at a tension speed of 200 mm / min and an atmospheric temperature of 23°C in accordance with JIS K7127, and the average values of 10 measured values were calculated.
[0134] (4) Total light transmittance, diffuse transmittance, haze The total light transmittance of the obtained heat shrinkable film was measured in accordance with JIS K7361-1 (1997), and the diffuse transmittance and haze value were measured in accordance with JIS K7136 (2000).
[0135] (5) Yellowness index (YI) The yellowness index (YI) of the obtained heat shrinkable film was measured in accordance with JIS K7373 (2006).
[0136] (6) Easy to cut by hand From each of the heat shrinkable films obtained in the Examples and Comparative Examples, a piece measuring 50 mm in the main shrinkage direction and 75 mm in the perpendicular direction was cut, and a 10 mm cut was made in the perpendicular direction at a position 25 mm from the main shrinkage direction. The cut film was then torn with fingertips in the perpendicular direction from the cut, and judged after three measurements according to the following criteria. [Evaluation Criteria] ○: No problem, or if resistance was felt along the way, but the cut was linearly cut in the perpendicular direction two or more times △: The film is cut to some extent, but the cut is wavy in the main shrinkage direction and is partially curved more than twice. ×: Almost no breaks, and the breaks are curved in the main shrinkage direction two or more times.
[0137] The raw materials used in each of the Reference Examples, Examples, and Comparative Examples are as follows. [Polyester resin (A)] A polyester resin consisting of 100 mol% terephthalic acid residue as dicarboxylic acid residue, and 65 mol% ethylene glycol residue, 32 mol% 1,4-cyclohexanedimethanol residue, and 3 mol% diethylene glycol residue as diol residues: glass transition temperature 78°C (hereinafter abbreviated as "PET-1") A polyester resin consisting of 70 mol% terephthalic acid residues, 30 mol% isophthalic acid residues as dicarboxylic acid residues, and 100 mol% ethylene glycol residues as diol residues: glass transition temperature 68°C (hereinafter referred to as "PET-2") A polyester resin consisting of 100 mol% terephthalic acid residues as dicarboxylic acid residues and 100 mol% 1,4-butanediol residues as diol residues: glass transition temperature 38°C (hereinafter abbreviated as "PBT-1")
[0138] <Reference example 1> According to the composition and configuration shown in Table 1, the raw materials used for layer (I) were mixed in a ratio of 58% by mass of "PET-1", 27% by mass of "PET-2", and 15% by mass of "PBT-1". In addition, the raw materials used for layer (II) were mixed in a ratio of 58% by mass of "PET-1", 27% by mass of "PET-2", and 15% by mass of "PBT-1". Thereafter, in a co-extrusion facility in which two twin-screw extruders, a conduit, a junction block, and a two-type three-layer multi-manifold nozzle were joined, the mixed raw materials were supplied to each twin-screw extruder with a set temperature of 250°C, and melt-kneaded in each extruder to co-extrude an unstretched sheet having a "layer (II) / layer (I) / layer (II)" configuration, which was taken up by a cast roll at 70°C and cooled and solidified to obtain an unstretched film. In addition, the ratio of the layer thickness of layer (I) to the total layer thickness was adjusted to be 75%. The unstretched film was then stretched in the TD at a stretch ratio of 5 times to obtain a heat-shrinkable film (packaging material) having a thickness of 20 μm in a film tenter apparatus set at a preheating temperature of 85 to 95° C., a stretching temperature of 83° C., and a heat treatment temperature of 96° C. Table 3 shows the evaluation results of the obtained heat-shrinkable film.
[0139] [Preparation of fluff using heat-shrinkable film (packaging material) without a printed layer as the starting material] The heat-shrinkable film obtained in Reference Example 1 was pulverized in a mechanical shearing pulverizer to obtain fluff having an average particle size of 5 mm (hereinafter, abbreviated as "Nf-1"). No heat treatment was performed in the pulverizer.
[0140] [Preparation of repellets using a heat-shrinkable film (packaging material) without a printed layer as the starting material] In a compounding facility equipped with a strand die attached to the tip of a twin-screw extruder set at 200°C, the fluff (Nf-1) obtained above was melt-kneaded while being forced into the feed hole of the twin-screw extruder using a Teflon (registered trademark) rod, and the discharged molten resin was formed into strands while being cooled in a water tank and cut into pellets using a pelletizer to obtain repellets (hereinafter abbreviated as "Nr-1").
[0141] The reduced viscosity measurement results, molecular weight measurement results, and composition analysis results of the obtained repellet (Nr-1) are shown in Table 2. The reduced viscosity was measured using an automatic viscosity measuring device. The molecular weight was measured using gel permeation chromatography (GPC). 20 mg of repellet (Nr-1) was dissolved in 4 mL of chloroform and 0.2 mL of hexafluoro-2-propanol, and 20 μL of the solution was injected, and the weight average molecular weight, number average molecular weight, and molecular weight distribution were measured in terms of standard polystyrene. The composition analysis was performed using a solvent of CDCl3, 1 This was measured by H-NMR.
[0142] [Preparation of Repellets (Pr) using heat-shrinkable film (packaging material) with a printed layer as the starting material] On one side of the heat-shrinkable film obtained in Reference Example 1, two colors, white ink and red ink, were printed all over. In addition, the other side, which was not printed all over, was overcoated with a (meth)acrylic resin to produce a heat-shrinkable film (P-1) having a printed layer. Then, the film end surface of the heat-shrinkable film (P-1) having a printed layer was solvent-sealed and cut into a size used for beverage labels. After that, the printing ink of the cut film was peeled off, and the film was recovered. As a result of checking the recovered film, the printing ink remained at about 3% of the film area. Next, the recovered film was dried for 24 hours in a hot air dryer set at 40°C, and the film from which the majority of the moisture had been removed was cut into a width of about 5 mm using a shredder to obtain a cut film. The cut film was then dried for 1 hour in a vacuum dryer set at 100°C. The amount of residual solvent in the cut film after vacuum drying was confirmed to be 1 ppm ethyl acetate, 13 ppm isopropyl alcohol, 36 ppm 1,3-dioxolane, 5 ppm propyl acetate, and 1 ppm 1-propanol. The amount of residual solvent was calculated from the peak area obtained by placing the cut film in a vial and heating it at 80°C for 30 minutes, and then measuring it by gas chromatography in the headspace. Next, in a compounding facility in which a strand die was attached to the tip of a twin-screw extruder set at 200°C, the vacuum-dried cut film was melt-kneaded while being pushed into the feed hole of the twin-screw extruder using a Teflon rod, and the discharged molten resin was stranded while being cooled in a water tank, and cut into pellets using a pelletizer. Through these processes, a repellet (Pr) (hereinafter abbreviated as "Pr-1") was obtained using the heat-shrinkable film (P-1) having a printed layer as the starting material.
[0143] The reduced viscosity measurement results, molecular weight measurement results, and composition analysis results of the obtained Repellet (Pr-1) are shown in Table 2. The reduced viscosity was measured using an automatic viscosity measuring device. The molecular weight was measured using gel permeation chromatography (GPC). 20 mg of Repellet (Pr-1) was dissolved in 4 mL of chloroform and 0.2 mL of hexafluoro-2-propanol, and 20 μL of the solution was injected, and the weight average molecular weight, number average molecular weight, and molecular weight distribution were measured in terms of standard polystyrene. The composition analysis was performed using a solvent of CDCl3, 1 This was measured by H-NMR. At this time, 1 In the H-NMR spectrum, signals not seen in the spectrum of the repellet (Nr-1) obtained above were seen at 0.8 to 0.9 ppm and 3.6 to 3.7 ppm. The former signal was a signal derived from the methyl group at the α-position of polymethyl methacrylate, and the latter was a signal derived from the methyl ester in the side chain of polymethyl methacrylate, so the content of the (meth)acrylic acid ester resin in the repellet (Pr-1) was calculated from the area of these signals.
[0144] [Preparation of fluff (Pf) using heat-shrinkable film (packaging material) with a printed layer as the starting material 1] On one side of the heat-shrinkable film obtained in Reference Example 1, two colors, white ink and red ink, were printed on the entire surface to produce a heat-shrinkable film (P-2) having a printed layer. At this time, overcoating was not performed on the other side that was not printed on the entire surface. Then, the end surface of the heat-shrinkable film (P-2) having a printed layer was sealed with a solvent and cut into a size used for beverage labels. Then, the printing ink of the cut film was peeled off, and the film was recovered. As a result of checking the recovered film, the printing ink remained at about 3% of the film area. Next, the recovered film was dried for 24 hours in a hot air dryer set at 40°C, and the film from which the rough moisture had been removed was pulverized to a particle size of about 10 mm using a mechanical shearing type pulverizer to obtain pulverized fluff. The ground fluff was then dried for 16 hours in a hot air dryer set at 80° C. Through these treatments, fluff (Pf) (hereinafter abbreviated as “Pf-1”) was obtained using the heat-shrinkable film (P-2) having a printed layer as the starting material. The amount of residual solvent in the pulverized fluff after hot air drying was confirmed to be 1 ppm isopropyl alcohol, 1 ppm 1,3-dioxolane, and 1 ppm propyl acetate. The amount of residual solvent was calculated from the peak area obtained by placing the cut film in a vial and heating it at 80°C for 30 minutes, and then measuring it by gas chromatography in the headspace.
[0145] The reduced viscosity measurement results, molecular weight measurement results, and composition analysis results of the obtained fluff (Pf-1) are shown in Table 2. The reduced viscosity was measured using an automatic viscosity measuring device. The molecular weight was measured using gel permeation chromatography (GPC). 20 mg of fluff (Pf-1) was dissolved in 4 mL of chloroform and 0.2 mL of hexafluoro-2-propanol, and 20 μL of the solution was injected to measure the weight average molecular weight, number average molecular weight, and molecular weight distribution in terms of standard polystyrene. The composition analysis was performed using a solvent of CDCl3, 1 This was measured by H-NMR. At this time, 1 In the 1 H-NMR spectrum, no signals were observed that were not observed in the spectrum of the repellet (Nr-1) obtained above, so no (meth)acrylic acid ester resin was contained.
[0146] [Preparation of fluff (Pf) using heat-shrinkable film (packaging material) with a printed layer as the starting material 2] An unknown heat-shrinkable label (P-3) (a cylindrical heat-shrinkable film whose edge was solvent-sealed) printed on one side with two colors, white and red ink, was stripped of its printing ink and the label was recovered. The recovered label was checked and found to have about 3% of the printing ink remaining on the film. The recovered label was then dried for 24 hours in a hot air dryer set at 40°C, and the film with most of the moisture removed was crushed to a particle size of about 10 mm using a mechanical shearing crusher to obtain crushed fluff. The ground fluff was then dried for 16 hours in a hot air dryer set at 80° C. Through these treatments, fluff (Pf) (hereinafter abbreviated as “Pf-2”) was obtained using the heat-shrinkable label (P-3) having a printed layer as the starting material. The amount of residual solvent in the pulverized fluff after hot air drying was confirmed to be 2 ppm isopropyl alcohol, 2 ppm 1,3-dioxolane, and 1 ppm propyl acetate. The amount of residual solvent was calculated from the peak area obtained by placing the cut film in a vial and heating it at 80°C for 30 minutes, and then measuring it by gas chromatography in the headspace.
[0147] The reduced viscosity measurement results, molecular weight measurement results, and composition analysis results of the obtained fluff (Pf-2) are shown in Table 2. The reduced viscosity was measured using an automatic viscosity measuring device. The molecular weight was measured using gel permeation chromatography (GPC). 20 mg of fluff (Pf-2) was dissolved in 4 mL of chloroform and 0.2 mL of hexafluoro-2-propanol, and 20 μL of the solution was injected to measure the weight average molecular weight, number average molecular weight, and molecular weight distribution in terms of standard polystyrene. The composition analysis was performed using a solvent of CDCl3, 1 This was measured by H-NMR. At this time, 1In the H-NMR spectrum, signals were observed at 0.8 to 0.9 ppm and 3.6 to 3.7 ppm. The former signal was derived from the methyl group at the α-position of polymethyl methacrylate, and the latter was derived from the methyl ester in the side chain of polymethyl methacrylate. From the areas of these signals, the content of the (meth)acrylic ester resin in the fluff (Pf-2) was calculated.
[0148] [Preparation of fluff (Pf) using heat-shrinkable film (packaging material) with a printed layer as the starting material 3] An unknown heat-shrinkable label (P-4) (a cylindrical heat-shrinkable film with the film edge sealed with a solvent) printed on one side with two colors, white and red ink, was subjected to a peeling process of the printing ink, and the label was recovered. When the recovered label was checked, it was found that about 3% of the printing ink remained on the film surface area. Next, the recovered label was dried for 24 hours in a hot air dryer set at 40°C, and the film with the bulk of the moisture removed was crushed into particles of about 10 mm using a mechanical shearing type crusher, and crushed fluff was obtained. The ground fluff was then dried for 16 hours in a hot air dryer set at 80° C. Through these treatments, fluff (Pf) (hereinafter abbreviated as “Pf-3”) was obtained using the heat-shrinkable label (P-4) having a printed layer as the starting material. When the amount of residual solvent in the pulverized fluff after hot air drying was checked, no residual solvents such as ethyl acetate, isopropyl alcohol, 1,3-dioxolane, propyl acetate, 1-propanol, etc. were found. The amount of residual solvent was measured by gas chromatography in the headspace after placing the cut film in a vial and heating it at 80°C for 30 minutes.
[0149] The reduced viscosity measurement results, molecular weight measurement results, and composition analysis results of the obtained fluff (Pf-3) are shown in Table 2. The reduced viscosity was measured using an automatic viscosity measuring device. The molecular weight was measured using gel permeation chromatography (GPC). 20 mg of fluff (Pf-3) was dissolved in 4 mL of chloroform and 0.2 mL of hexafluoro-2-propanol, and 20 μL of the solution was injected to measure the weight average molecular weight, number average molecular weight, and molecular weight distribution in terms of standard polystyrene. The composition analysis was performed using a solvent of CDCl3, 1 This was measured by H-NMR. At this time, 1 In the 1 H-NMR spectrum, no signals were observed at 0.8 to 0.9 ppm and 3.6 to 3.7 ppm, indicating that no (meth)acrylic acid ester resin was contained.
[0150] <Example 1> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that the raw materials used for the layer (I) were a mixture of 44 mass% "PET-1", 20 mass% "PET-2", 11 mass% "PBT-1", and 25 mass% "Pr-1". The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0151] <Example 2> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that the raw materials used for the layer (I) were a mixture of 44 mass% "PET-1", 20 mass% "PET-2", 11 mass% "PBT-1", and 25 mass% "Pf-1". The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0152] <Example 3> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that the raw materials used for the layer (I) were a mixture of 44 mass% "PET-1", 20 mass% "PET-2", 11 mass% "PBT-1", and 25 mass% "Pf-2". The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0153] <Example 4> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that the raw materials used for the layer (I) were a mixture of 29 mass% "PET-1", 14 mass% "PET-2", 7 mass% "PBT-1" and 50 mass% "Pf-2". The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0154] <Example 5> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that the raw materials used for the layer (I) were a mixture of 44 mass% "PET-1", 20 mass% "PET-2", 11 mass% "PBT-1", and 25 mass% "Pf-3". The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0155] <Example 6> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that the raw materials used for the layer (I) were a mixture of 29 mass% of "PET-1," 14 mass% of "PET-2," 7 mass% of "PBT-1," and 50 mass% of "Pf-3." The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0156] <Comparative Example 1> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that "Pr-1" was mixed at a ratio of 100 mass% as the raw material used for the layer (I). The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0157] <Reference example 2> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that the raw materials used for the layer (I) were a mixture of 44 mass% "PET-1", 20 mass% "PET-2", 11 mass% "PBT-1", and 25 mass% "Nr-1". The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0158] <Reference example 3> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that the raw materials used for the layer (I) were a mixture of 44 mass% "PET-1", 20 mass% "PET-2", 11 mass% "PBT-1", and 25 mass% "Nf-1". The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0159] <Reference example 4> A heat-shrinkable film having a thickness of 20 μm was obtained in the same manner as in Reference Example 1, except that "Nr-1" was mixed at a ratio of 100 mass% as the raw material used for the layer (I). The evaluation results of the obtained heat-shrinkable film are shown in Table 3.
[0160] [Table 1]
[0161] [Table 2]
[0162] [Table 3]
[0163] The heat shrinkable films of Examples 1 to 6 have a light transmittance of 85% or more at a measurement wavelength of 400 nm in spectrophotometric measurement, and furthermore, at any measurement wavelength between 400 nm and 800 nm, the light transmittance is 85% or more, so that no impairment of appearance due to coloration was observed. Furthermore, it can be seen from the results in Table 3 that the heat shrinkable films of Examples 1 to 6 have excellent shrink properties and mechanical strength. In terms of transparency, the films also had excellent transparency, with high total light transmittance and low haze values. Furthermore, the absolute value of the yellowness index (YI) was also small. Furthermore, the heat-shrinkable films obtained in Examples 1 to 6 have shrinkage characteristics, mechanical properties, transparency and color equivalent to those of a heat-shrinkable film obtained only from virgin raw materials as exemplified in Reference Example 1, a heat-shrinkable film containing repellets made from a heat-shrinkable film having no printed layer as a starting material as exemplified in Reference Example 2, and a heat-shrinkable film containing fluff made from a heat-shrinkable film having no printed layer as a starting material as exemplified in Reference Example 3. This shows that the heat-shrinkable films of Examples 1 to 6 are heat-shrinkable films having excellent characteristics and performance, similar to conventional heat-shrinkable films. Furthermore, the heat shrinkable films of Examples 3 to 6 had excellent hand-tearability.
[0164] On the other hand, the heat shrinkable film of Comparative Example 1 was clearly reddish in the visual appearance evaluation compared to the heat shrinkable films of Examples 1 to 6, and was a film with impaired appearance. This is believed to be because the light transmittance of the heat shrinkable film of Comparative Example 1 was less than 85% at a measurement wavelength of 400 nm, which is outside the range specified by the present invention, and the properties and performance of the heat shrinkable film were significantly deteriorated. In addition, the heat shrinkable film of Comparative Example 1 had a significantly decreased MD tensile elongation at break, and did not have the mechanical strength required for a heat shrinkable film. Furthermore, the haze value of the heat shrinkable film of Comparative Example 1 increased significantly, and did not have the transparency required for a heat shrinkable film. Furthermore, the significant deterioration in the characteristics and performance of the heat-shrinkable film of Comparative Example 1 is clear when compared with a heat-shrinkable film containing repellets made from the unprinted heat-shrinkable film as the starting material, as exemplified in Reference Example 4.
[0165] The present invention has been described above in relation to the embodiment that is considered to be the most practical and preferable at present. However, the present invention is not limited to the embodiment disclosed in the specification of this application, and can be modified as appropriate within the scope of the claims and the gist or concept of the invention that can be read from the entire specification, and heat-shrinkable films with such modifications should also be understood to be included within the technical scope of the present invention. [Industrial Applicability]
[0166] The heat-shrinkable film of the present invention has high transparency, excellent appearance, heat shrinkability, break resistance, impact resistance and rigidity, and therefore can be suitably used as a packaging material for food, beverage, pharmaceutical and medical packaging, chemical product, cosmetic packaging, toiletry packaging, industrial packaging and agricultural supplies, and can be suitably used as a packaging material for these applications.
Claims
1. A method for producing a heat-shrinkable film having an overcoat and a printing layer containing a (meth)acrylic ester resin, and at least one layer (I) made of a resin composition (Z1) containing at least one of fluff (Pf) and repellet (Pr) obtained from a packaging material (P) containing a polyester resin (A) as a main component as a starting material, the method comprising the steps of: (a) subjecting the packaging material (P) to at least one of a printing ink peeling treatment (a), a cutting treatment (b), a crushing treatment (c) and a drying treatment (d) to reduce the amount of fluff (Pf) and repellet (Pr) and producing a heat-shrinkable film using a resin composition (Z1) containing at least one of the obtained fluff (Pf) and repellet (Pr), wherein the resin composition (Z1) contains a polyester-based resin (A) as a main component, the content of at least one of the fluff (Pf) and repellet (Pr) in the resin composition (Z1) is 20 mass% or more and 70 mass% or less, and the resin composition (Z1) contains 0.6 mass% or less of the (meth)acrylic acid ester-based resin.
2. 2. The method for producing a heat-shrinkable film according to claim 1, wherein the packaging material (P) is a heat-shrinkable film.
3. 3. The method for producing a heat-shrinkable film according to claim 1, wherein the packaging material (P) is attached to a molded product or a container.
4. The method for producing a heat-shrinkable film according to any one of claims 1 to 3, wherein the heat-shrinkable film has a tensile elongation at break in a direction perpendicular to a main shrinkage direction of 34% or more.
5. The method for producing a heat shrinkable film according to any one of claims 1 to 4, wherein the polyester resin (A) contains a terephthalic acid residue as a dicarboxylic acid residue.
6. The method for producing a heat shrinkable film according to any one of claims 1 to 5, wherein the polyester resin (A) contains an ethylene glycol residue as a diol residue.
7. The method for producing a heat-shrinkable film according to any one of claims 1 to 6, wherein the polyester-based resin (A) contains, as a diol residue, at least one selected from a 1,4-cyclohexanedimethanol residue, a neopentyl glycol residue, a 1,4-butanediol residue, and a diethylene glycol residue.
8. The method for producing a heat-shrinkable film according to any one of claims 1 to 7, wherein the polyester resin (A) contains, as a diol residue, at least one of a 1,4-cyclohexanedimethanol residue and a neopentyl glycol residue as an essential component.
9. The method for producing a heat-shrinkable film according to any one of claims 1 to 8, wherein the heat-shrinkable film has a heat shrinkage rate of 30% or more in the main shrinkage direction when immersed in warm water at 100°C for 10 seconds.
10. The method for producing a heat shrinkable film according to any one of claims 1 to 9, wherein the heat shrinkable film has a tensile modulus in a main shrinkage direction of 5,500 MPa or less.
11. The method for producing a heat-shrinkable film according to any one of claims 1 to 10, wherein the heat-shrinkable film comprises at least two layers, a layer (II) made of a resin composition (Z2) not containing a raw material made of the packaging material (P) and the layer (I).
12. The method for producing a heat shrinkable film according to claim 11, wherein the resin composition (Z2) contains the polyester resin (A) as a main component.
13. The method for producing a heat-shrinkable film according to claim 12, wherein the polyester resin (A) contained in the resin composition (Z2) contains, as a diol residue, at least one of a 1,4-cyclohexanedimethanol residue and a neopentyl glycol residue.
Citation Information
Patent Citations
Manufacture of heat-shrinkable film
JP1994047810A
Polyester film and method for peeling printed ink
JP2002060518A
Thermally shrinkable polyester-based film
JP2012036273A